EXAMINING STUDENTS’ SPEAKING SKILL THROUGH CLASS DISCUSSION - Swantika, Ika; Harissandi, Refin; Anwar, Rossya Diva (Jurnal Review Pendidikan dan Pengajaran, 2024)
The aims of this study are to find out the the students’ difficulties in speaking english in class discussion. Class discussions provide a framework for students to think critically out loud about topics being covered in class. They also provide an opportunity to gauge how well the students are comprehending course concepts, assignments, and outside readings. Descriptive qualitative design was conducted in this study. The subjects of this study are the students from the Teknologi Informatika STMIK Pelita Nusantara Medan. The data were collected by doing observation and recording the students’ utterances in class discussion. From the research, it was found the students got some problems in communicating when they were having a class discussion . There were two factors causing them got difficulties in speaking English when they were having a class discussion. The first factor was the Linguistic Problem, some linguistic problems were of lack of vocabularies, lack of practicing, and lack of grammatical knowledge. The second factor was Psychological Problem. Psychological problems are those problems, which often interference the emotional or physical health. These psychological problems may bring negative effect towards student’s speaking performance. Over a quarter of a million people in this world have problems towards their confidence.